A Model for the High-Energy Emission from Blazars - Reynoso, Matias Miguel (2012)
We study the production of VHE emission in blazars as a superposition of a steady a component from a baryonic jet, and a time-dependent contribution from an inner e-e+ beam launched by the black hole. Both primary electrons and protons are injected near the base of the jet, and the particle distributions along it are found solving a stationary one-dimensional transport equation accounting for convection and cooling. The short-timescale variability of the emission is explained by perturbations introduced by Kelvin-Helmholtz (KH) instabilities and their interaction with relativistic shocks. For illustration purposes, we apply the model to the case of PKS 2155-304.